Effectivity of Jatropha multifida L. Leaves Extract as Antibacterial on Streptococcus mutans using In Vitro Testing Methods - Kinasih, Listyaning Kartiko; Idamawati Nababan; Suci Erawati; Rouli Natasia M Simanjuntak (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Intoduction: Health is the condition of the entire body and body parts of an individual who is free from disease both physically, mentally and socially, thus enabling the individual to be able to carry out daily activities more productively. However, many people neglect their own health, especially in the field of dental and oral health. Caries is one of the most common oral and dental problems. The prevalence of dental caries in Indonesia is high, namely 88.8%. Dental caries is caused by Streptococcus mutans bacteria which plays a role in the conversion of sucrose to lactic acid. Infection due to Streptococcus mutans bacteria can be treated by taking antibiotics. Apart from drugs, antibiotics can also be obtained from natural ingredients, one of which is the tintir castor plant (Jatropha multifida Linn) or commonly known as the betadine. Objective: To see the effect of the antibacterial content of tintir leaves against Streptococcus mutans bacteria and to determine the differences in the antibacterial effect of betadine leaf extract (Jatropha multifida L.) from a concentration of 25%, 50%, 75%, and 100% against Streptococcus mutans. Methods: The type of research used in this study was a laboratory experimental study with a post-test-only control group design as the research design and to test the sensitivity of bacteria using the paper disc diffusion test. Data analysis using One-Way ANOVA. Result: The results of this study indicate the effect of tintir castor leaf extract (Jatropha multifida L.) in inhibiting the growth of Streptococcus mutans bacteria.